Single Photon Emitters Coupled to Plasmonic Waveguides: A Review. Issue 10 (2nd September 2021) - Kumar, Shailesh; Bozhevolnyi, Sergey I.
Abstract: During the last two decades, many research groups have demonstrated coupling of single photon emitters to plasmonic waveguides, promising very high emission enhancements, for applications in quantum technologies. In this review, recent developments within this important research topic are discussed. Different plasmonic waveguide–quantum emitter configurations are compared from the application viewpoint by utilizing a figure‐of‐merit (FOM) reflecting the emission enhancement, coupling efficiency, and radiation loss. The experimental methods applied to obtain the coupled systems with high FOMs are described. Configurations that are exploited for reinforcing the coupling efficiency, i.e., the efficiency of funneling the emitted radiation into a plasmonic waveguide, are also considered as well as the scalability potential of various waveguide platforms. A recent experiment, in which enhanced light–matter interaction in a plasmonic waveguide is taken advantage of, resulting in the demonstration of non‐linearity at the single emitter level, is discussed. Abstract : In this review, various single photon emitter (SPE) – plasmonic waveguide (PW) coupled systems are compared using a figure‐of‐merit, reflecting the emission enhancement, coupling efficiency, and radiation loss. The fabrication methods, advantages, disadvantages and scalability issues of the coupled systems are discussed. Other structures that have been utilized to aid the emission channeling from SPEs into the PWs are also described.